Epidemic-induced changes in nursing students’ professional identity: a qualitative investigation - Zhang, Huiting; He, Wenhao; Cao, Dan; Liu, Jiali; Yang, Yongfeng; Zhu, Xiaoli; Jiang, Mengxiao (Frontiers in Public Health, 2025)
ObjectiveTo explore the impact and mechanisms of COVID-19 on the professional identity of nursing students, providing theoretical and practical insights to inform nursing education reform.MethodThis study employed Colaizzi’s descriptive phenomenological method to explore nursing students’ experiences. Semi-structured interviews were conducted, and data collection continued until information saturation was achieved. Data analysis followed Colaizzi’s seven-step approach: (1) reading all participants’ descriptions to gain a general understanding, (2) extracting significant statements, (3) formulating meanings from these statements, (4) organizing formulated meanings into clusters of themes, (5) developing an exhaustive description, (6) refining the description into a fundamental structure, and (7) validating the findings by returning to participants for feedback. A socialization theory framework was applied to analyze relationships between themes and clarify the mechanisms underlying professional identity development.ResultsFrom March 1 to March 13, 2023, 21 nursing students from seven medical schools in Guangdong Province participated in the research. The findings showed that nursing students’ professional identity, initially medium or low before the epidemic, significantly improved afterward. Three key themes related to professional identity improvement were identified based on socialization theory: (1) Social Practice Experience: Activities such as volunteer services and pandemic prevention education promote role affirmation, meaningful engagement, and a strong professional mission. (2) Role Model Observation: Observing frontline healthcare workers enhances professional honor and role expectations. (3) Social Comparison and Evaluation: Positive feedback from media, family, and peers encourages respect and enthusiasm for nursing.ConclusionThe COVID-19 pandemic markedly improved nursing students’ professional identity, providing insights for education and career development. To strengthen nursing education, it is advised to emphasize disaster response training, integrate role model examples, and utilize social recognition to foster students’ professional identity and commitment.